A study of real-time operating systems for microcomputers - Wells, George Clifford (Rhodes University, Faculty of Science, Department of Computer Science, 1990)
This thesis describes the evaluation of four operating systems for microcomputers. The emphasis of the study is on the suitability of the operating systems for use in real-time applications, such as process control. The evaluation was performed in two sections. The first section was a quantitative assessment of the performance of the real-time features of the operating system. This was performed using benchmarks. The criteria for the benchmarks and their design are discussed. The second section was a qualitative assessment of the suitability of the operating systems for the development and implementation of real-time systems. This was assessed through the implementation of a small simulation of a manufacturing process and its associated control system. The simulation was designed using the Ward and Mellor real-time design method which was extended to handle the special case of a real-time simulation. The operating systems which were selected for the study covered a spectrum from general purpose operating systems to small, specialised real-time operating systems. From the quantitative assessment it emerged that QNX (from Quantum Software Systems) had the best overall performance. Qualitatively, UNIX was found to offer the best system development environment, but it does not have the performance and the characteristics required for real-time applications. This suggests that versions of UNIX that are adapted for real-time applications are worth careful consideration for use both as development systems and implementation systems.
Keywords: Operating systems (Computers); Microcomputers